2023
DOI: 10.3390/foods12020413
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Crop Yield Reduction in China under 1.5 °C and 2 °C Global Warming from CMIP6 Models

Abstract: Warmer temperatures significantly influence crop yields, which are a critical determinant of food supply and human well-being. In this study, a probabilistic approach based on bivariate copula models was used to investigate the dependence (described by joint distribution) between crop yield and growing season temperature (TGS) in the major producing provinces of China for three staple crops (i.e., rice, wheat, and maize). Based on the outputs of 12 models from the Coupled Model Intercomparison Project Phase 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…They also observed that the highest decrease in yield is anticipated in the highest emission scenario (ssp585) compared to the medium (ssp245) and lower (ssp126) scenarios in the Songnen Plains. Additionally, Wang et al (2023a) confirmed that the rising temperatures projected under the CMIP6 model have a greater detrimental effect on rice and wheat production in Sichuan province, as well as on maize production in Shandong province.…”
Section: Future Projections Of Air Temperaturesmentioning
confidence: 53%
See 3 more Smart Citations
“…They also observed that the highest decrease in yield is anticipated in the highest emission scenario (ssp585) compared to the medium (ssp245) and lower (ssp126) scenarios in the Songnen Plains. Additionally, Wang et al (2023a) confirmed that the rising temperatures projected under the CMIP6 model have a greater detrimental effect on rice and wheat production in Sichuan province, as well as on maize production in Shandong province.…”
Section: Future Projections Of Air Temperaturesmentioning
confidence: 53%
“…The surface air temperature observed in 2022 was the second-highest recorded temperature in China since 1961, providing evidence that China is experiencing increasing warmth as a result of climate change (Wang et al, 2022). The rise in air temperature has adversely affected crop production in numerous regions of China, with the coastal area being particularly vulnerable to the effects of increasing temperatures (Chandio et al, 2022;Saud et al, 2022;Wang et al, 2023a). According to the findings of Chandio et al (2022), the increasing air temperatures have had a significant negative impact on rice and wheat production in Sichuan province.…”
Section: Future Projections Of Air Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The first differencing, as suggested in previous studies 23 , 65 , was applied as a technique to detrend the maize yield to account for the other yield impacting unobserved factors such as advancement in agricultural technology, progression of the adjustments in growers according to the management recommendations, and the infrastructural developments. The data on aforesaid factors was not available.…”
Section: Methodsmentioning
confidence: 99%